The simple sea is a musical tributary for "pro" art (Journal of the College of Basic Education, 2022)
Al-Muwalia is an art of ancient folk poetry and I put to sing; When it contains a box of Maalamatmusical instruments made him more amenable to singing; his words are static in the last in the filling; Some of what you useIt may be Arabized that does not include melody, or it may be melody that does not include arabic, and the melody in it is betterand elegant, as well as its mostly bisected metrical construction - simple bisected - which is consistent withWhat male and female singers want from light and short melodies that are suitable for singing and the basis of its musical structureA metrical development in Bahour Al-Khaliliya, especially in its use of the dividing pattern and the use ofThe correct activation (fa’an) in his performances and hits, which is not possible in poetryThe eloquent is nothing but an anomaly, as it is the development and diversification of rhymes on the one hand; and the rules of syntax